Platelets and Inflammation: Relations between Platelet Counts and Markers of Inflammation - Nirmay Sonar; Varun Bafna; Priyamvada Singh; Iftikar Khadas; Mansi Chavan (European Scientific Journal, ESJ, 2021)
Platelets, or thrombocytes are small non-nucleated cells that are primarily responsible for the formation of the platelet plug, and consequently in primary hemostasis. However, their role is not limited only to a response to cell injury, but they also respond to systemic inflammation. Due to factors such as a shared lineage with other cells of the blood, recent studies showing the molecular expression of immune modulators on platelets, and the release of inflammatory molecules leading to chemoattraction by responder molecules. These implications may also go deeper into the pathogenesis of cancers in the human body, and quantification of that relation, platelets with inflammation, is the aim of the study